Chlorpromazine Efficiently Treats the Crisis of Pheochromocytoma: Four Case Reports and Literature Review - Wang, James Jiqi; He, Zuowen; Yang, Yan; Yu, Bo; Wang, Hong; Ding, Hu; Cui, Guanglin; Wang, Luyun; Wang, Dao Wen; Jiang, Jiangang (Frontiers in Cardiovascular Medicine, 2021)
Pheochromocytoma multisystem crisis (PMC) is a potentially lethal emergency due to catecholamine secretion. The condition manifests as severe hypertension to intractable cardiogenic shock and has a high mortality rate. This study explored the efficacy and safety of applying chlorpromazine on PMC patients. The study included seven patients (median age, 42 years; range, 14–57 years) diagnosed with pheochromocytoma. Four consecutive PMC patients were admitted to our critical care unit between 2016 and 2020 due to abdominal or waist pain, nausea, and vomiting. Their blood pressure (BP) fluctuated between 200–330/120–200 and 40–70/30–50 mmHg. Chlorpromazine (25 or 50 mg) was injected intramuscularly, followed by continuous intravenous infusion (2-8 mg/h). The patients’ BP decreased to 100–150/60–100 mmHg within 1–3 h and stabilized within 3–5 days. Two weeks later, surgical tumor resection was successfully performed in all four patients. Similar clinical outcomes were also obtained in three patients with sporadic PMC reported in the literature who received chlorpromazine treatment, which reduced their BP readings from >200/100 mmHg to 120/70 mmHg. Our observations, combined with sporadic reports, showed that chlorpromazine efficiently controlled PMC. Thus, future studies on the use of chlorpromazine are warranted.